Do mothers who delivered at health facilities return to health facilities for postnatal care follow-up? A multilevel analysis of the 2016 Ethiopian Demographic and Health Survey. - Brhane Ayele; Mulugeta Woldu; Haftom Gebrehiwot; Tsegay Wellay; Tsegay Hadgu; Hailay Gebretnsae; Alemnesh Abrha; Equbay Gebre-Egziabher; Sarah Hurlburt (PLoS ONE)
Introduction Returning to health facility for postnatal care (PNC) use after giving birth at health facility could reflect the health seeking behavior of mothers. However, such studies are rare though they are critically important to develop vigorous strategies to improve PNC service utilization. Therefore, this study aimed to determine the magnitude and factors associated with returning to health facilities for PNC among mothers who delivered in Ethiopian health facilities after they were discharged. Methods This cross-sectional study used 2016 Ethiopian Demographic and Health Survey data. A total of 2405mothers who gave birth in a health facility were included in this study. Multilevel mixed-effect logistic regression model was fitted to estimate both independent (fixed) effects of the explanatory variables and community-level (random) effects on return for PNC utilization. Variable with p-value of ≤ 0.25 from unadjusted multilevel logistic regression were selected to develop three models and p-value of ≤0.05 was used to declare significance of the explanatory variables on the outcome variable in the final (adjusted) model. Analysis was done using IBM SPSS statistics version 21. Result In this analysis, from the total 2405 participants, 14.3% ((95%CI: 12.1-16.8), (n = 344)) of them returned to health facilities for PNC use after they gave birth at a health facility. From the multilevel logistic regression analysis, being employed (AOR = 1.51, 95%CI: 1.04-2.19), receiving eight and above antenatal care visits (AOR = 2.90, 95%CI: 1.05-8.00), caesarean section delivery (AOR = 2.53, 95%CI: 1.40-4.58) and rural residence (AOR = 0.56, 95%CI: 0.36-0.88) were found significantly associated with return to health facilities for PNC use among women who gave birth at health facility. Conclusion Facility-based PNC utilization among mothers who delivered at health facilities is low in Ethiopia. Both individual and community level variables were determined women to return to health facilities for PNC use. Thus, adopting context-specific strategies/policies could improve PNC utilization and should be paid a due focus.